Monitoring two-stage processes with a profile at the second stage. Issue 3 (16th March 2017) - Esmaeeli, Hamid; Sadegheih, Ahmad; Amiri, Amirhossein; Doroudyan, Mohammad Hadi
ABSTRACT: In the multistage processes, quality of a process or a product at each stage is related to the previous stage(s). This property is referred to as a cascade property. Sometimes, quality of a process is characterized by a profile. In this paper, we consider a two-stage process with a normal quality characteristic in the first stage and a simple linear regression profile in the second stage. Then we propose two methods to monitor quality characteristics in both stages. The performance of the proposed two methods is evaluated through a numerical example in terms of average run length criterion.